Rangeland monitoring using point line intercept in southern Tunisia - Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2024)
The image v illustrates the process of rangeland monitoring through the application of the point line intercept method in the southern regions of Tunisia. This method involves systematically placing a transect line across the rangeland and recording the points of intersection between the line and vegetation at specified intervals. It serves as a valuable tool for assessing vegetation composition, distribution, and density, offering valuable insights into the overall health and productivity of the rangeland ecosystem.